Assessment of cardıac sparıng ın radıotherapeutıc management of medıastınal Hodgkın lymphoma (hl) durıng chıldhood and adolescence - Assessment of cardıac sparıng ın radıotherapeutıc management of medıastınal Hodgkın lymphoma (hl); adolescence (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Lymphomas constitute the most frequent hematologic malignancies. HL is a rare type of B cell lymphoma featured with Reed Sternberg cells. Treatment of HL may be considered among the greatest success stories in oncology. Improvements in treatment of HL have rendered quality of life an important aspect of management given the long life expectancy of younger patients, particularly the children and adolescents.  The heart may be partly exposed to irradiation in radiotherapeutic management of mediastinal HL. Late effects of irradiation may include stenosis, regurgitation, and fibrosis of the cardiac conduction pathways which may result in late onset arrhythmias and conduction defects, angina pectoris, valvular disorders, coronary artery disease and myocardial infarction. Patients receiving RT to the mediastinum may suffer from adverse cardiovascular effects of irradiation due to coronary atherosclerosis formation which may occur despite the lack of any cardiovascular risk factors, and an asymptomatic period of several years may precede presentation with coronary heart disease given the slow process of intimal hyperplasia and collagen deposition. It may take several years after RT to diagnosis of these complications. Normal tissue sparing Radiation Therapy (RT) techniques allow for improved targeting and normal tissue sparing in HL management. A relatively newer breakthrough has been the introduction of proton therapy with its unique characteristics. Herein, we provide a concise review of evolving RT techniques for management of mediastinal HL with focus on cardiac sparing.